2014
DOI: 10.1681/asn.2013091004
|View full text |Cite
|
Sign up to set email alerts
|

Renal Outcomes in Patients with Type 1 Diabetes and Macroalbuminuria

Abstract: Macroalbuminuria, defined as urine albumin excretion rate (AER)$300 mg/d, has long been considered a stage of irreversible kidney damage that leads reliably to GFR loss. We examined the long-term renal outcomes of persons with type 1 diabetes who developed incident macroalbuminuria during the Diabetes Control and Complications Trial (DCCT)/Epidemiology of Diabetes Interventions and Complications (EDIC) study. One hundred fifty-nine participants developed incident macroalbuminuria and were subsequently followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 36 publications
1
62
0
4
Order By: Relevance
“…It also is associated with a high cumulative incidence of ESRD (75%) at 15 years of follow-up [14]. A recent study reporting on long-term renal outcomes in patients with type 1 diabetes who developed incident macroalbuminuria during the DCCT trial found that the cumulativeincidences of chronic kidney disease (CKD) and ESRD were only 32 and 16%, respectively, 10 years after diagnosis [15]. This supports the observation that reductions in AER are common, with more than half of type 1 diabetic patients with macroalbuminuria regressing to persistent AER <300 mg/day after long-term follow-up.…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…It also is associated with a high cumulative incidence of ESRD (75%) at 15 years of follow-up [14]. A recent study reporting on long-term renal outcomes in patients with type 1 diabetes who developed incident macroalbuminuria during the DCCT trial found that the cumulativeincidences of chronic kidney disease (CKD) and ESRD were only 32 and 16%, respectively, 10 years after diagnosis [15]. This supports the observation that reductions in AER are common, with more than half of type 1 diabetic patients with macroalbuminuria regressing to persistent AER <300 mg/day after long-term follow-up.…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…Although not an ideal biomarker of renal risk, the presence of microalbuminuria has been linked to an increased risk for both cardiovascular events and progression of kidney disease in patients with type 2 diabetes. Macroalbuminuria is more consistently associated with an elevated risk of both renal and cardiovascular complications [2,3]. Therefore, regular assessment of albuminuria remains a clinical cornerstone to diagnose the onset of kidney disease in diabetes and to prospectively track the progression of renal injury.…”
Section: Introductionmentioning
confidence: 99%
“…Bei optimaler Einstellung (HbA1c < 7) kam es nach 25 Jahren zu einer 36-bis 76-prozentigen Reduktion der mikrovaskulären Komplikationen im Vergleich zur Gruppe mit einem HbA1c~9 % [3]. Die Inzidenz der terminalen Niereninsuffizienz in der intensiv behandelten Gruppe lag bei 11/1000 Patienten [4]. Sobald entweder eine Hypertonie oder eine Albuminurie (ab Stadium A2) vorliegt, gilt die medikamentöse RAAS-Blockade als Therapiegesichert [5,6].…”
Section: Die Nierenerkrankung Bei Patienten Mit Diabetes Mellitus I (unclassified